Modeling water resources management at the basin level: methodology and application to the Maipo River Basin - Cai, Ximing; Ringler, Claudia; Rosegrant, Mark W. (International Food Policy Research Institute, 2006)
With increasing competition for water across sectors and regions, the river basin has been recognized as the appropriate unit of analysis for addressing the challenges of water resources management. Modeling at this scale can provide essential information for policymakers in their resource allocation decisions... This report presents the methodology development of an integrated economic–hydrologic river-basin model, as well as the application of this prototype to the Maipo River Basin in Chile. The model is based on a node-link river-basin network, including multiple source nodes (reservoirs, aquifers, river reaches, and so on) and demand sites, for municipal and industrial (M&I), hydropower, and agricultural water demands.